REVIEW: POTENSI SECANG (Caesalpinia sappan L.) DALAM TERAPI ARTRITIS REUMATOID - Fauzia Indah Sabila; Tukiran Tukiran (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2021)
Artritis reumatoid (AR) is a chronic inflammatory disease caused by inflammatory mediators that migrate to synovial and particular tissues. The disease is characterized by synovial inflammation that leads to the destruction of cartilage and joint damage. Although conventional treatments of AR such as NSAID, corticosteroid and DMARDs commonly alleviate the symptoms of AR, but the high edverse of these treatments leads AR patients toward alternative medicine. The purpose of the present review is to evaluate the potential of secang in rheumatoid arthritis therapy. Various phytochemical components of secang provide pharmacological effects such as antioxidant activity in suppressing oxidative stress as a promoter for disease, including inflammation. Anti-inflammatory and anti-arthritis activities of secang are able to inhibit pro-inflammatory cytokine regulation and cartilage degradation in AR. The pharmacological effect of secang has the potential to be used as a functional food or supplement in the therapy of AR by preventing, treating and repairing the damage caused by AR.. Key words: Anti-arthritis, Anti-infammatory, Anti-oxidant, Artritis Reumatoid, Caesalpinia sappan L.